2005
DOI: 10.1093/bja/aei250
|View full text |Cite
|
Sign up to set email alerts
|

Single-injection thoracic paravertebral block for postoperative pain treatment after thoracoscopic surgery †

Abstract: We conclude that single-shot preoperative paravertebral block improves post-operative pain treatment after thoracoscopic surgery in a clinically significant fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
90
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 24 publications
11
90
0
11
Order By: Relevance
“…Many methods of pain management, each with attendant problems, have been tried with varied success, for example: intercostal nerve block (1;2), intrapleural analgesia (3;4), cryoanalgesia (5;6), lumbar epidural (7;8), thoracic epidural (9;10), paravertebral block (11)(12)(13), IV narcotics (8;14;15), intrathecal (16)(17)(18) or epidural (2;15;19;20) narcotics, NSAIDS (1;21;22), and transcutaneous nerve stimulation (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Many methods of pain management, each with attendant problems, have been tried with varied success, for example: intercostal nerve block (1;2), intrapleural analgesia (3;4), cryoanalgesia (5;6), lumbar epidural (7;8), thoracic epidural (9;10), paravertebral block (11)(12)(13), IV narcotics (8;14;15), intrathecal (16)(17)(18) or epidural (2;15;19;20) narcotics, NSAIDS (1;21;22), and transcutaneous nerve stimulation (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Paravertebral blockade is a regional anaesthetic technique that can be used for analgesia after thoracic surgery [1][2][3][4], cardiac surgery [5], breast surgery [6][7][8] or upper abdominal surgery [9], or for chronic pain therapy [10]. A thoracic paravertebral block is performed by injecting local anaesthetic solution into the paravertebral space, which contains the thoracic nerves, their branches and the sympathetic trunk.…”
mentioning
confidence: 99%
“…Gulbahar et al [14] compared epidural and Para vertebral continuous block for elective posterolateral thoracotomy and concluded that both the technique are equally effective in post-operative pain management. Detterbeck et al [15] conducted a review of prospective, randomized studies for pain relief after thoracotomy.…”
Section: Discussionmentioning
confidence: 99%